99mTc-sestamibi : Clinical applications - Ahmadzadehfar, Hojjat; Biersack, Hans-Jürgen; Bucerius, Jan (Springer Berlin Heidelberg, 2012)
99mTc-sestamibi is a single-photon emission computed tomography (SPECT) radiotracer that was introduced into clinical routine for myocardial perfusion imaging more than two decades ago. Although today the main application of 99mTc-sestamibi SPECT remains the imaging of myocardial perfusion, it is also an accepted and well-proven imaging technique for a variety of oncologic and non-oncologic applications, including brain, breast, and thyroid cancer and thyroid and parathyroid adenoma. Its efficacy in a range of indications ensures that 99mTc-sestamibi SPECT will remain widely used despite the rapid diffusion of 18F-FDG PET.                         99mTc-Sestamibi - Clinical Applications provides a detailed and informative overview of almost all the oncologic and non-oncologic applications of 99mTc-sestamibi SPECT, including several relatively rare indications. Different disease-related protocols for 99mTc-sestamibi SPECT are presented, and for each disease a comprehensive summary of the relevant pathology and epidemiology is provided. Throughout, there is a strong emphasis on the practical aspects of use of this popular tracer, including instructions for the preparation of several commercially available tracer kits. Clinical practitioners will find this book to be an invaluable guide to the application and benefits of 99mTc-sestamibi SPECT in both the inpatient and the outpatient setting.